First interferometric study of enhanced N-fractionation in N2H+: the high-mass star-forming region IRAS 05358+3543. Issue 4 (16th March 2019) - Colzi, L; Fontani, F; Caselli, P; Leurini, S; Bizzocchi, L; Quaia, G
Abstract: Nitrogen (N)-fractionation is used as a tool to search for a link between the chemical history of the Solar system and star-forming regions. A large variation of 14 N/ 15 N is observed towards different astrophysical sources, and current chemical models cannot reproduce it. With the advent of high angular resolution radiotelescopes it is now possible to search for N-fractionation at core scales. We present IRAM NOEMA observations of the J = 1–0 transition of N2 H +, 15 NNH +, and N 15 NH + towards the high-mass protocluster IRAS 05358+3543. We find 14 N/ 15 N ratios that span from ∼100 up to ∼220 and these values are lower or equal to those observed with single-dish observations towards the same source. Since N-fractionation changes across the studied region, this means that it is regulated by local environmental effects. We find also the possibility, for one of the four cores defined in the protocluster, to have a more abundant 15 NNH + with respect to N 15 NH + . This is another indication that current chemical models may be missing chemical reactions or may not take into account other mechanisms, like photodissociation or grain surface chemistry, that could be important.